Tradisi Grebeg Gethuk: Studi tentang Kendala dan Keberlanjutan Tradisi Grebeg Gethuk di Kota Magelang - Azahro, Sekar Aprilia; Suyanto, Edy; Windiasih, Rili (YASIN, 2025)
Grebeg Gethuk is a distinctive tradition of Magelang City that highlights the traditional food getuk as a symbol of regional cultural identity. The uniqueness of this tradition has earned Magelang the nickname “City of Getuk” and strengthened the image of local culture within the community. This study aims to fill the gap in research concerning the challenges in implementing the Grebeg Gethuk tradition, while also describing its execution and the preventive strategies adopted by the Department of Education and Culture. A qualitative descriptive method was used, drawing on primary and secondary data obtained through interviews, observation, and documentation. The findings reveal that the implementation of Grebeg Gethuk faces several obstacles, including the impact of the Covid-19 pandemic, miscommunication among stakeholders, and budget constraints. Nevertheless, the spirit of cultural preservation remains strong, supported by collaboration among the government, community, artists, and getuk producers. Preventive strategies include enhancing cross-sectoral coordination, optimizing budget use, and introducing innovative adaptations of the tradition in response to current conditions. The study concludes that the continuity of Grebeg Gethuk relies heavily on the collaboration and commitment of all stakeholders to preserve this tradition as a form of living and relevant local wisdom in the modern era.